Benchmarking the value of care: Variability in hospital costs for common operations and its association with procedure volume. Issue 5 (May 2020) - Zogg, Cheryl K.; Bernard, Andrew C.; Hirji, Sameer A.; Minei, Joseph P.; Staudenmayer, Kristan L.; Davis, Kimberly A.
Abstract : Supplemental digital content is available in the text. Abstract : BACKGROUND: Efforts to improve health care value (quality/cost) have become a priority in the United States. Although many seek to increase quality by reducing variability in adverse outcomes, less is known about variability in costs. In conjunction with the American Association for the Surgery of Trauma Healthcare Economics Committee, the objective of this study was to examine the extent of variability in total hospital costs for two common procedures: laparoscopic appendectomy (LA) and laparoscopic cholecystectomy (LC). METHODS: Nationally weighted data for adults 18 years and older was obtained for patients undergoing each operation in the 2014 and 2016 National Inpatient Sample. Data were aggregated at the hospital-level to attain hospital-specific median index hospital costs in 2019 US dollars and corresponding annual procedure volumes. Cost variation was assessed using caterpillar plots and risk-standardized observed/expected cost ratios. Correlation analysis, variance decomposition, and regression analysis explored costs' association with volume. RESULTS: In 2016, 1, 563 hospitals representing 86, 170 LA and 2, 276 hospitals representing 230, 120 LC met the inclusion criteria. In 2014, the numbers were similar (1, 602 and 2, 259 hospitals). Compared with a mean of US $10, 202, LA median costs ranged from US $2, 850 to US $33, 381. Laparoscopic cholecystectomy median costs ranged from US $4, 406 to US $40, 585 with a mean of US $12, 567. Differences in cost strongly associated with procedure volume. Volume accounted for 9.9% (LA) and 12.4% (LC) of variation between hospitals, after controlling for the influence of other hospital (8.2% and 5.0%) and patient (6.3% and 3.7%) characteristics and in-hospital complications (0.8% and 0.4%). Counterfactual modeling suggests that were all hospitals to have performed at or below their expected median cost, one would see a national cost savings of greater than US $301.9 million per year (95% confidence interval, US $280.6–325.5 million). CONCLUSION: Marked variability of median hospital costs for common operations exists. Differences remained consistent across changing coding structures and database years and were strongly associated with volume. Taken together, the findings suggest room for improvement in emergency general surgery and a need to address large discrepancies in an often-overlooked aspect of value. LEVEL OF EVIDENCE: Epidemiological, level III.